Rationalizable Suicides: Evidence from Changes in Inmates' Expected Length of Sentence - Nadia Campaniello; Theodoros Diasakos; Giovanni Mastrobuoni (Institute for the Study of Labor (IZA), 2014)
Is there a rational component in the decision to commit suicide? Economists have been trying to shed light on this question by studying whether suicide rates are related to contemporaneous conditions. This paper goes one step further: we test whether suicides are linked to forward-looking behavior. In Italy, collective sentence reductions (pardons) often lead to massive releases of prisoners. More importantly, they are usually preceded by prolonged parliamentary activity (legislative proposals, discussion, voting, etc.) that inmates seem to follow closely. We use the legislative proposals for collective pardons to measure changes in the inmates' expectations about the length of their sentences, and find that suicide rates tend to be significantly lower when par- dons are proposed in congress. This suggests that, amongst inmates in Italian prisons, the average decision to commit suicide responds to changes in current expectations about future conditions. At least partially, therefore, the decision seems rationalizable.
Keywords: I1; D1; K4; 330; suicides; rationality; prisons; collective pardons